Cervical and Oral Screening for HR-HPV types 16 and 18 among Sudanese Women Cervical Lesions - Elasbali, Abdelbaset Mohamed (BioMed Central, 2012)
OBJECTIVE: This study examined whether there is a positive correlation existed between cervical and oral High Risk-Human Papilloma Viruses (HR-HPV) types 16, 18 infections in patients with clinically confirmed cervical lesions. METHODS: In this study 50 participants were included (40 were cases and 10 were controls). One hundred DNA materials (50 were cervical and 50 were oral epithelial tissues) were analyzed using HR-HPV subtypes 16 and 18 specific PCR probes. RESULTS: Of the 40 cases, HR-HPV 16, 18 were identified in 16/40 (40%), of the cervical tissues of whom 8/16 (50%) were positive for HPV 16; 6/16 (37.5%) were identified with HR-HPV 18, and 2/16 (12.5%) were detected with both HR-HPV subtypes. All of the clinically healthy cases were found negative. Only one oral tissue sample (case) was 1/40 (2.5%) was found positive for HPV subtype16. CONCLUSION: The frequency of infection with HR-HPV subtypes 16 and 18 is high among Sudanese women with cervical lesions and suggests a role of HR-HPV in the development of cervical cancer in Sudan. No correlation between cervical and oral HPV infection was noted. Further study with screening of large number of patients with cervical cancer is recommended for further clarification of these findings.